Short-run dynamics and long-run effects of demographic change on public debt and the budget - Volker Ulrich; Manfred Erbsland (Universität Greifswald, Rechts- und Staatswissenschaftliche Fakultät, 1998)
The German population is aging. Since fewer children are born and simultaneously life expectancy rises, demographic changes will lead to a double aging process. The paper analyzes the effects of demographic changes on national debt and the public budget by applying a cointegration analysis to global budget variables. Our procedure which covers the period between 1950 and 1990 completes prevailing projections, emphasizing that low vital rates are not the basic problem but the long-run trend of decreasing fertility and mortality rates. The estimation results of several error- correction models show that in the long-run an increase in the old age dependency ratio, and a decrease in the reproduction rate will lead to higher public expenditures. As regards public revenue, the results are ambivalent. The change in the age structure results in higher tax revenue, whereas the decline of population has the opposite effect. Furthermore, we find empirical evidence that aging increases the debt ratio. This development counters current efforts to reduce the public debt share of production potential and the tax load ratio. As a consequence, more action is needed to improve Germany's competiveness as a business location. Compared to these long-run effects, the short-run dynamics is only of minor importance. Significant parameter estimates can be found mainly in the model for the social security contribution rate.
Keywords: 330